EM4 SEBAGAI AGEN PENGOLAHAN SAMPAH ORGANIK: MEWUJUDKAN PEMBERDAYAAN MASYARAKAT YANG RAMAH LINGKUNGAN DI RW 07 KELURAHAN MANGGAHANG - Syahira Fahreza Risdiana; Perkasa, Agus; Anna Rinjani Sulistiono; Fachri Aprian; Mustaqim (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2025)
Garbage is a common problem and is the most complained about by the people of RW 07, Manggahang Village, Baleendah District, Bandung Regency. To overcome this waste problem, a socialization program was implemented for processing organic waste using EM4 which has many benefits. EM4 is a culture of microorganisms that is beneficial for plant growth. The method used is SISDAMAS where community assistance is provided so that the program can be carried out sustainably in the future. The results obtained are the socialization activity was carried out on Monday, August 26 at the RW 07 office and was attended by the community such as RW officials, PKK mothers and other members of the public. The socialization flow includes introductions and fertilizer making demonstrations. The socialization went smoothly with high public enthusiasm and it is hoped that this socialization can provide knowledge to the public about EM4 and also organic waste processing to create a clean and waste-free environment.